2010
DOI: 10.1016/b978-0-12-381300-8.00007-1
|View full text |Cite
|
Sign up to set email alerts
|

Bronchus-Associated Lymphoid Tissue (BALT)

Abstract: Bronchus-associated lymphoid tissue (BALT) is a constitutive mucosal lymphoid tissue adjacent to major airways in some mammalian species, including rats and rabbits, but not humans or mice. A related tissue, inducible BALT (iBALT), is an ectopic lymphoid tissue that is formed upon inflammation or infection in both mice and humans and can be found throughout the lung. Both BALT and iBALT acquire antigens from the airways and initiate local immune responses and maintain memory cells in the lungs. Here, we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
194
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(213 citation statements)
references
References 201 publications
6
194
0
5
Order By: Relevance
“…Differences between mouse and rat towards LPS treatment may be likely related to differences in their mucosal immune systems, such as the presence of BALT, and subsequently FAE in rats, but not in normal mouse. 43 In fact, TLR-4 and MHC Class II detected in bronchiolar FAE from control rats suggests that LPS uptake may occur in this compartment during the onset of lung inflammation. In parallel, we showed a predominant CD68 macrophage infiltrate in bronchioles, similar to another study, 44 but no lymphocytic or polymorphonuclear (neutrophilic) response was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between mouse and rat towards LPS treatment may be likely related to differences in their mucosal immune systems, such as the presence of BALT, and subsequently FAE in rats, but not in normal mouse. 43 In fact, TLR-4 and MHC Class II detected in bronchiolar FAE from control rats suggests that LPS uptake may occur in this compartment during the onset of lung inflammation. In parallel, we showed a predominant CD68 macrophage infiltrate in bronchioles, similar to another study, 44 but no lymphocytic or polymorphonuclear (neutrophilic) response was observed.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, the close vicinity detected in our LPS model between bronchiole goblet cells and interstitial macrophages allow us to hypothesize that-beside any direct cell-cell interaction-soluble factors released by those macrophages may contribute also to modulate via a basolateral pathway the phenotype of bronchiolar goblet cells. Because of structural differences between the rat and human airway mucosal immune systems represented by the absence of BALT in healthy humans, 43 we decided to further validate our hypothesis in a human-based model rather than in rats stimulating in-vitro primary culture of HBEC with supernatants from human MDM challenged with or without LPS.…”
Section: Discussionmentioning
confidence: 99%
“…14,37 These lymphoid aggregates develop in response to chronic immune stimulation, which, in this case, may have been a Figures 13-14. Lymphoplasmacytic cuffs, lung, Norway rats.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary infection in mice with pathogens such as influenza virus (9), murine herpesvirus 68 (12), Mycobacterium tuberculosis (31), modified vaccinia virus Ankara (32), or repetitive inhalations of heat-killed Pseudomonas aeruginosa (33) induced iBALT. These iBALTs contain myeloid DCs, a network of stromal cells, and FDCs within the B-cell follicles (12,32,34). The formation of HEVs and lymphatic vessels facilitates the recirculation of lymphocytes (35).…”
Section: Discussionmentioning
confidence: 99%